KONTRIBUSI DISIPLIN BELAJAR DAN LINGKUNGAN SEKOLAH TERHADAP HASIL BELAJAR SISWA KELAS XE SMKN 5 PADANG PADA MATA PELAJARAN DASAR LISTRIK DAN ELEKTRONIKA TAHUN AJARAN 2012/2013 - Havizatil Usni Usni; Ahmad Jufri; H. Sukaya (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2014)
This research based on the problem of low report study to DLE subject from some student of class XE at SMKN 5 Padang, wich 41,67% student got result of study below Kriteria Ketuntasan Minimal (KKM). The standard of KKM to DLE subject is 75 with scale from 0-100. The purpose of this research is to show the contribution of student discipline of study and school environment toward study report of DLE subject from students of class XE at SMKN 5 Padang. This research is a correlational research which is descriptive. The population of this research is 96 student and sample consist of 49 students class XE at SMKN 5 Padang on 2012/2013. The technique of sampling was using simple random sampling. The data of student report taken from teacher of DLE subject at SMKN 5 Padang while data of student discipline of study and school environment collected through questionnaire by using likert scale. Analysis of data is using statistic method with the help of Microsoft Exell 2007 software. The result of data analysis shows: (1) student discipline of study give contribution as 26,89% to student report of SMKN 5 Padang on 2012/2013. (2) School environment give contribution as 24,32 to student report of SMKN 5 Padang on 2012/2013. (3) Discipline of study and school environment simultancously give contribution as 36,03% to student report of SMKN 5 Padang on 2012/2013. Keywords: Discipline of study, school environtment, study report, correlational descriptive, simple random sampling.